Pengaruh Pola Pikir dan Pola Hidup Pasca Covid- 19: Telaah Singkat Ledakan Home Sweet Home Perspektif Rhenald Kasali - Fani Putri Amaliya; Sofiana Saidah; Ahmad Sholikin; Masduki Asbari (Literaksi: Jurnal Manajemen Pendidikan, 2023)
The purpose of this research is to find out the Effect of Covid-19 on the Environment from Rhenald Kasali's youtube channel entitled "Home Sweet Home Explosion by Rhenald Kasali". The author uses a descriptive qualitative method by taking notes because the source of the data is obtained by listening to oral narratives. The result of this study is that Covid-19 has become a historic moment for the whole world which has almost weakened the wheel of life. The impact during the pandemic was a crisis with the environmental system, meaning that there was a relationship between the Covid-19 outbreak and environmental damage, this study also mentions social distancing during a pandemic, meaning that during a pandemic people prefer to work from home, making them more productive, and a lot of time with family.